Anti-corrosion energy storage cable

By using multi-layer twisted conductor structure, central reinforcement and high-performance sheathing materials in energy storage cables, combined with surface treatment technology, the problems of insufficient corrosion resistance and poor tensile and compressive properties of traditional energy storage cables are solved, and higher mechanical properties and longer service life are achieved.

CN119786126AActive Publication Date: 2025-04-08JIANGSU HONGFENG CABLE GROUP

Patent Information

Application Number
CN202510000927.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Traditional energy storage cables have aging and cracking due to insufficient anti-corrosion performance during long-term use, which in turn causes the conductor and insulation layer to be corroded, affecting the electrical performance of the cable, and perform poorly in tensile, compressive and wear resistance, resulting in a shortened service life.

Method used

The multi-layer twisted conductor structure is adopted, including soft annealed copper wire and specially treated high-strength aluminum alloy wire, combined with high-strength carbon fiber rods as the central reinforcement, and high-performance thermoplastic polyurethane elastomer and materials such as polytetrafluoroethylene micropowder and aramid fiber are used in the sheath layer. Through surface treatment technologies such as tin plating and nanotitanium dioxide coating, the cable's corrosion resistance, tensile and compressive resistance and wear resistance are improved.

Benefits of technology

It significantly improves the tensile strength of the conductor and the overall mechanical properties of the cable, enhances the corrosion and wear resistance of the sheath, extends the service life of the cable, and improves reliability in complex and harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786126A_ABST
    Figure CN119786126A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-corrosion type energy storage cable, and relates to the technical field of cables, the anti-corrosion type energy storage cable comprises a conductor layer, an anti-compression layer, a sheath layer and a connecting part, the conductor layer comprises a tensile rope, the outer surface of the tensile rope is provided with a wire A, the outer surface of the wire A is sleeved with a wire B, the outer surface of the wire B is provided with a shielding sleeve, and the shielding sleeve is arranged on the outer surface of the cable. The outer surface of the shielding sleeve is sleeved with an insulating sleeve, the compression-resistant layer comprises an inner protective plate, a supporting frame is fixedly installed on the outer surface of the inner protective plate, an outer protective plate is fixedly installed on the outer surface of the supporting frame, a buffer block is arranged between the outer protective plate and the inner protective plate, and a woven belt is arranged on the outer surface of the outer protective plate. According to the invention, through the design of the sheath A made of a composite material, the situation that the electrical performance of the cable is affected by the corrosion of the conductor and the insulating layer due to the aging and cracking of the sheath caused by the corrosion of the cable in the long-term use process of the cable is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, and in particular to an anti-corrosion energy storage cable. Background Art

[0002] This article focuses on anti-corrosion energy storage cables, and deeply explores their innovative designs in terms of corrosion resistance, tensile and compressive resistance, and wear resistance. Through the careful design of three innovative points, including the use of new composite materials as sheaths, the optimization of the internal reinforcement structure of the cable, and the use of special surface treatment technology, the structural composition of each innovative point and the excellent functions it brings are elaborated in detail. These innovations are aimed at comprehensively improving the reliability and durability of anti-corrosion energy storage cables in complex and harsh environments, so as to meet the increasingly stringent performance requirements of energy storage systems for cables, and provide solid technical support for the efficient and stable development of the energy storage industry.

[0003] The cable disclosed in the publication number CN110473669B includes a conductor assembly (102), the conductor assembly having a first conductor (110), a second conductor (112), and an insulator (114) surrounding the first conductor and the second conductor. The insulator has an outer surface (116). The conductor assembly extends the length of the cable (100) along a longitudinal axis. The first conductor (110) has a first core (200) and a first conductive layer (202) on the first core (200). The second conductor (112) has a second core (220) and a second conductive layer (222) on the second core (220). The first core and the second core (200, 220) are dielectrics. The cable (100) includes a cable shield (120) around the conductor assembly (102), the cable shield engages the outer surface (116) of the insulator (114), and provides electrical shielding for the first conductor and the second conductor (110, 112). The cable shield (120) extends along the longitudinal axis.

[0004] In the existing technology, as the global demand for clean energy continues to grow, energy storage technology, as a key link to ensure the stable supply and efficient utilization of energy, has been rapidly developed. As the core component of power transmission in energy storage systems, energy storage cables have extremely complex and diverse working environments. In many energy storage application scenarios, cables not only face the corrosion threat of various chemical substances, but also need to withstand mechanical stresses such as stretching, compression, and frequent friction and wear during installation and operation. In the long-term use of traditional energy storage cables, it is often easy to cause sheath aging and cracking due to insufficient anti-corrosion performance, which in turn causes corrosion to the conductor and insulation layer, affecting the electrical performance of the cable; at the same time, the limitations in tensile, compressive and wear resistance also greatly reduce its service life in harsh environments, and may even cause safety accidents. Therefore, the research and development of new energy storage cables with excellent anti-corrosion, tensile, compressive and wear resistance has extremely important practical significance and broad application prospects.

[0005] Therefore, we propose an anti-corrosion energy storage cable to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide an anti-corrosion energy storage cable to solve the problem that traditional photovoltaic cables mentioned in the above background technology are often prone to aging and cracking of the sheath due to insufficient anti-corrosion performance during long-term use, thereby causing corrosion of the conductor and insulation layer and affecting the electrical performance of the cable.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: an anti-corrosion energy storage cable, comprising a conductor layer, a pressure-resistant layer, a sheath layer and a connecting component: the conductor layer comprises a tensile rope, the outer surface of the tensile rope is provided with a conductor A, the outer surface of the conductor A is provided with a conductor B, the outer surface of the conductor B is provided with a shielding sleeve, the outer surface of the shielding sleeve is provided with an insulating sleeve, the pressure-resistant layer comprises an inner protective plate, the outer surface of the inner protective plate is fixedly installed with a support frame, the outer surface of the support frame is fixedly installed with an outer protective plate, a buffer block is provided between the outer protective plate and the inner protective plate, and the outer surface of the outer protective plate is provided with a braided belt; by adopting a multi-layer twisted conductor structure, for example, the inner layer adopts soft annealed copper wire to ensure good conductivity; the outer layer is twisted with specially treated high-strength aluminum alloy wire, the surface of the aluminum alloy wire is nickel-plated to improve its corrosion resistance and oxidation resistance, this multi-layer twisted structure significantly improves the tensile strength of the conductor while ensuring good conductivity of the conductor, when the cable is subjected to tensile force, the outer layer of aluminum alloy wire can bear most of the tensile force , protecting the inner copper wire from damage; by setting a high-strength carbon fiber rod as a central reinforcement at the center of the conductor layer, the carbon fiber rod has extremely high strength and modulus, is light in weight and has good corrosion resistance. It can provide additional support and tensile strength for the conductor, effectively preventing the conductor from breaking or deforming when subjected to large tensile force. At the same time, the low thermal expansion coefficient of the carbon fiber rod helps to reduce the internal stress changes of the conductor caused by temperature changes and improve the stability of the conductor; the inner guard plate, support frame and outer guard plate are made of polypropylene, which has high corrosion resistance, good mechanical strength and excellent electrical insulation performance, and polypropylene is often used in light support frames, which is suitable for cables with high requirements for temperature resistance and corrosion resistance; by wrapping a layer of high-strength polyester braided tape around the outside of the insulation layer, the polyester braided tape has good mechanical properties, and its high strength and high toughness can provide effective protection for the insulation layer when the cable is squeezed or bent by external force to prevent the insulation layer from being damaged. At the same time, the mesh structure of the braided tape can also disperse external forces to a certain extent and reduce local stress concentration.

[0008] Preferably, the conductor A adopts a multi-layer twisted structure, and its material is soft annealed copper wire, the material of the conductor B is nickel-plated aluminum alloy wire, and the material of the tensile rope is carbon fiber rod.

[0009] Preferably, the shielding sleeve is made of aluminum foil, the insulating sleeve is made of natural rubber, and the braided belt is made of polyester.

[0010] Preferably, the shapes of the inner guard plate, the outer guard plate and the interior of the buffer block are all honeycomb-shaped, and the materials of the inner guard plate, the support frame and the outer guard plate are all polypropylene.

[0011] Preferably, the number of the buffer blocks is eight groups, and the eight groups of buffer blocks are evenly distributed between the inner guard plate and the outer guard plate, and the material of the buffer blocks is polyurethane foam.

[0012] Preferably, the sheath layer includes a sheath A, the outer surface of the sheath A is coated with a coating A, and the outer surface of the coating A is coated with a coating B; by selecting a high-performance thermoplastic polyurethane elastomer as the base polymer, the thermoplastic polyurethane elastomer has a unique microphase separation structure, consisting of a hard segment and a soft segment, the hard segment provides strength and wear resistance, and the soft segment gives the material good flexibility and elasticity. This structure enables the thermoplastic polyurethane elastomer to have high mechanical properties while maintaining excellent flexural resistance, and can adapt to the deformation requirements of the cable under different working conditions; by adding polytetrafluoroethylene powder as an anti-corrosion additive. Polytetrafluoroethylene has extremely excellent chemical inertness and is highly tolerant to almost all strong acids, strong alkalis, strong oxidants and organic solvents. Its micro-powder form can be evenly dispersed in the thermoplastic polyurethane elastomer matrix to form a microscopic anti-corrosion barrier. When the cable sheath is corroded by corrosive media, the polytetrafluoroethylene micro-powder can prevent the penetration of corrosive ions and effectively protect the integrity of the sheath material. By introducing high-strength aramid fiber as a reinforcing material, aramid fiber has ultra-high strength and modulus, and its strength is several times that of steel wire. It also has good heat resistance and chemical corrosion resistance. The aramid fiber is evenly distributed in a high-performance thermoplastic polyurethane elastomer matrix in a specific weaving method or in the form of short fibers, which can significantly improve the tensile strength and tear resistance of the sheath material. By adding an appropriate amount of benzotriazole anti-ultraviolet agents, this type of anti-ultraviolet agent can absorb ultraviolet energy and convert it into harmless heat energy and dissipate it, effectively preventing ultraviolet rays from causing photoaging of the sheath material and extending the service life of the sheath.

[0013] Preferably, the material of the sheath A is thermoplastic polyurethane elastomer as a base polymer, polytetrafluoroethylene is added as an anti-corrosion additive, high-strength aramid fiber is introduced as a reinforcing material, and an appropriate amount of benzotriazole anti-ultraviolet agent is added therein, and the material of the coating A is ceramic.

[0014] Preferably, the material of the coating B is polyurethane containing a microcapsule repair agent.

[0015] Preferably, the surface sheath B of one end of the wire A and the wire B connected to the connecting component, and the outer surfaces of the connecting component and the sheath B are coated with a coating C.

[0016] Preferably, the surface of the sheath B is tin-plated, and the material of the coating C is nano-titanium dioxide; the surfaces of the wires A, B and the connecting parts are first tin-plated to form a dense tin protective layer, tin has high chemical stability, good corrosion resistance in general acid and alkali environments, and can effectively prevent the copper conductor from being corroded, and then the tin-plated layer is passivated to further improve its corrosion resistance and antioxidant properties. The passivation treatment can form a dense oxide film on the surface of the tin-plated layer to prevent corrosive substances from directly contacting the tin layer; by using nanotechnology to coat a layer of nano-titanium dioxide coating on the surface of the connecting part, the nano-coating has excellent antibacterial and anti-fouling properties, and can prevent the surface of the connecting part from corrosion and poor contact caused by microbial growth or dirt accumulation. At the same time, the super-hydrophilic or super-hydrophobic properties of the nano-coating can be adjusted according to actual needs. For example, the super-hydrophobic nano-coating can make the surface of the connecting part have a self-cleaning function and reduce the adhesion of moisture and corrosive substances on the surface.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention, when in use, adopts a multi-layer twisted conductor structure, for example, the inner layer adopts soft annealed copper wire to ensure good conductivity; the outer layer adopts specially treated high-strength aluminum alloy wire for twisting, and the surface of the aluminum alloy wire is nickel-plated to improve its corrosion resistance and oxidation resistance. This multi-layer twisted structure not only ensures good conductivity of the conductor, but also significantly improves the tensile strength of the conductor. When the cable is subjected to tensile force, the aluminum alloy wire of the outer layer can bear most of the tensile force and protect the copper wire of the inner layer from damage; a high-strength carbon fiber rod is arranged at the center of the conductor layer as a central reinforcement. The carbon fiber rod has extremely high strength and modulus, is light in weight, and has good corrosion resistance. It can provide additional support and tensile strength for the conductor, effectively preventing the conductor from being damaged when subjected to tensile force. When subjected to a large tensile force, the conductor will break or deform. At the same time, the low thermal expansion coefficient of the carbon fiber rod helps to reduce the internal stress changes of the conductor caused by temperature changes and improve the stability of the conductor. The inner guard plate, support frame and outer guard plate are made of polypropylene, which has high corrosion resistance, good mechanical strength and excellent electrical insulation performance. Polypropylene is often used in light support frames and is suitable for cables with high requirements for heat resistance and corrosion resistance. A layer of high-strength polyester braided tape is wrapped around the outside of the insulation layer. The polyester braided tape has good mechanical properties. Its high strength and high toughness can provide effective protection for the insulation layer when the cable is squeezed or bent by external force to prevent the insulation layer from being damaged. At the same time, the mesh structure of the braided tape can also disperse external forces to a certain extent and reduce local stress concentration.

[0019] 2. When used, the present invention selects a high-performance thermoplastic polyurethane elastomer as a base polymer. The thermoplastic polyurethane elastomer has a unique microphase separation structure, which is composed of a hard segment and a soft segment. The hard segment provides strength and wear resistance, and the soft segment gives the material good flexibility and elasticity. This structure allows the thermoplastic polyurethane elastomer to have high mechanical properties while maintaining excellent flexural resistance, and can adapt to the deformation requirements of the cable under different working conditions; polytetrafluoroethylene powder is added as an anti-corrosion additive. Polytetrafluoroethylene has extremely excellent chemical inertness and is highly tolerant to almost all strong acids, strong alkalis, strong oxidants and organic solvents. Its micro-powder form can be evenly dispersed in the thermoplastic polyurethane elastomer matrix to form a microscopic anti-corrosion barrier. When the cable sheath is corroded by corrosive media, the polytetrafluoroethylene micro-powder can prevent the penetration of corrosive ions and effectively protect the integrity of the sheath material. By introducing high-strength aramid fiber as a reinforcing material, aramid fiber has ultra-high strength and modulus, and its strength is several times that of steel wire. It also has good heat resistance and chemical corrosion resistance. The aramid fiber is evenly distributed in a high-performance thermoplastic polyurethane elastomer matrix in a specific weaving method or in the form of short fibers, which can significantly improve the tensile strength and tear resistance of the sheath material. By adding an appropriate amount of benzotriazole anti-ultraviolet agents, this type of anti-ultraviolet agent can absorb ultraviolet energy and convert it into harmless heat energy and dissipate it, effectively preventing ultraviolet rays from causing photoaging of the sheath material and extending the service life of the sheath.

[0020] 3. When the present invention is used, the surfaces of the wires A and B and the connecting parts are first tin-plated to form a dense tin protective layer. Tin has high chemical stability and good corrosion resistance in general acid and alkaline environments, and can effectively prevent the copper conductor from being corroded. Then, the tin-plated layer is passivated to further improve its corrosion resistance and antioxidant properties. The passivation treatment can form a dense oxide film on the surface of the tin-plated layer to prevent corrosive substances from directly contacting the tin layer. A layer of nano-titanium dioxide coating is coated on the surface of the connecting part using nanotechnology. The nano-coating has excellent antibacterial and anti-fouling properties, and can prevent the surface of the connecting part from corrosion and poor contact caused by microbial growth or dirt accumulation. At the same time, the super-hydrophilic or super-hydrophobic properties of the nano-coating can be adjusted according to actual needs. For example, the super-hydrophobic nano-coating can make the surface of the connecting part have a self-cleaning function and reduce the attachment of moisture and corrosive substances on the surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A cross-sectional view of an anti-corrosion energy storage cable of the present invention;

[0022] Figure 2 This is a schematic diagram of the explosion structure at the conductor layer in an anti-corrosion energy storage cable of the present invention;

[0023] Figure 3 The present invention is an anti-corrosion energy storage cable Figure 2 Schematic diagram of the explosion structure at A in the middle;

[0024] Figure 4 This is a schematic diagram of the explosion structure at the conductor layer and the pressure-resistant layer in an anti-corrosion energy storage cable of the present invention;

[0025] Figure 5 The present invention is an anti-corrosion energy storage cable Figure 4 The enlarged view of point B in the middle;

[0026] Figure 6 This is a schematic diagram of the explosion structure at the sheath layer of an anti-corrosion energy storage cable of the present invention;

[0027] Figure 7 It is a schematic diagram of the explosion structure of the sheath B and the coating C when the conductor A and the conductor B are connected to the connecting component in an anti-corrosion energy storage cable of the present invention;

[0028] Figure 8 The present invention is an anti-corrosion energy storage cable Figure 7 Enlarged view of point C in the middle

[0029] In the figure: 100, conductor layer; 200, pressure-resistant layer; 300, sheath layer; 101, tensile rope; 102, wire A; 103, wire B; 104, shielding sleeve; 105, insulating sleeve; 201, inner protective plate; 202, support frame; 203, outer protective plate; 204, buffer block; 205, braided belt; 301, sheath A; 302, coating A; 303, coating B; 400, connecting component; 401, sheath B; 402, coating C. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the implementation regulations described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1: Reference Figure 1-3As shown: an anti-corrosion energy storage cable, including a conductor layer 100, a pressure-resistant layer 200, a sheath layer 300 and a connecting component 400: the conductor layer 100 includes a tensile rope 101, the outer surface of the tensile rope 101 is provided with a conductor A102, the outer surface of the conductor A102 is sleeved with a conductor B103, the outer surface of the conductor B103 is provided with a shielding sleeve 104, the outer surface of the shielding sleeve 104 is sleeved with an insulating sleeve 105, the pressure-resistant layer 200 includes an inner protective plate 201, the outer surface of the inner protective plate 201 is fixedly mounted with a support frame 202, the outer surface of the support frame 202 is fixedly mounted with an outer protective plate 203, a buffer block 204 is provided between the outer protective plate 203 and the inner protective plate 201, and the outer surface of the outer protective plate 203 is provided with a braided belt 205, The conductor A102 adopts a multi-layer twisted structure, and its material is soft annealed copper wire, the conductor B103 is made of nickel-plated aluminum alloy wire, the tensile rope 101 is made of carbon fiber rod, the shielding sleeve 104 is made of aluminum foil, the insulating sleeve 105 is made of natural rubber, the braided belt 205 is made of polyester, the inner shape of the inner guard plate 201, the outer guard plate 203 and the buffer block 204 are all honeycomb-shaped, the inner guard plate 201, the support frame 202 and the outer guard plate 203 are all made of polypropylene, the number of the buffer block 204 is eight groups, and the eight groups of buffer blocks 204 are evenly distributed between the inner guard plate 201 and the outer guard plate 203, and the material of the buffer block 204 is polyurethane foam, and the polyurethane foam filling material plays an important buffering role inside the cable. When the cable is subjected to external impact, such as collision during transportation or accidental impact by heavy objects at the installation site, the polyurethane foam material can absorb and disperse the impact energy, reducing the damage to the internal conductor and the insulation layer. For example, in a simulation test of a cable falling from a height, the damage to the internal conductor and insulation layer of the cable containing polyurethane foam filling material is significantly lower than that of the unfilled cable. At the same time, the polyurethane foam fills the internal gaps of the cable, making the cable structure more compact, which to a certain extent also helps to improve the overall compression resistance of the cable and prevent the internal structure of the cable from displacement or deformation when it is under pressure.

[0032] In this embodiment, a multi-layer twisted conductor structure is adopted, for example, the inner layer adopts soft annealed copper wire to ensure good conductivity; the outer layer adopts specially treated high-strength aluminum alloy wire for twisting, and the surface of the aluminum alloy wire is nickel-plated to improve its corrosion resistance and oxidation resistance. This multi-layer twisted structure can significantly improve the tensile strength of the conductor while ensuring good conductivity of the conductor. When the cable is subjected to tensile force, the aluminum alloy wire of the outer layer can bear most of the tensile force and protect the copper wire of the inner layer from damage;

[0033] By arranging a high-strength carbon fiber rod as a central reinforcement at the center of the conductor layer 100, the carbon fiber rod has extremely high strength and modulus, is light in weight, and has good corrosion resistance. It can provide additional support and tensile strength for the conductor, effectively preventing the conductor from breaking or deforming when subjected to a large tensile force. At the same time, the low thermal expansion coefficient of the carbon fiber rod helps to reduce the internal stress changes of the conductor caused by temperature changes, thereby improving the stability of the conductor.

[0034] The inner protective plate 201, the support frame 202 and the outer protective plate 203 are made of polypropylene, which has high corrosion resistance, good mechanical strength and excellent electrical insulation performance. Polypropylene is often used in light support frames 202 and is suitable for cables with high requirements for temperature resistance and corrosion resistance.

[0035] By wrapping a layer of high-strength polyester braided tape 205 outside the insulation layer, the polyester braided tape 205 has good mechanical properties. Its high strength and high toughness can provide effective protection for the insulation layer when the cable is squeezed or bent by external force to prevent the insulation layer from being damaged. At the same time, the mesh structure of the braided tape 205 can also disperse external forces to a certain extent and reduce local stress concentration.

[0036] Embodiment 2: Figure 4-6 As shown, the sheath layer 300 includes a sheath A301, the outer surface of the sheath A301 is coated with a coating A302, the outer surface of the coating A302 is coated with a coating B303, the material of the sheath A301 is thermoplastic polyurethane elastomer as a base polymer, and polytetrafluoroethylene is added as an anti-corrosion additive, high-strength aramid fiber is introduced as a reinforcing material, and an appropriate amount of benzotriazole anti-ultraviolet agent is added therein, the material of the coating A302 is ceramic, the material of the coating B303 is polyurethane containing a microcapsule repair agent, the weight percentage of the thermoplastic polyurethane elastomer is: 60-70%; polytetrafluoroethylene powder: 15-20%; aramid fiber: 10-15%; benzotriazole anti-ultraviolet agent: 3-5%, and the uniform dispersion of polytetrafluoroethylene powder in the sheath material forms a strong anti-corrosion defense line. In an acidic environment, such as in a sulfuric acid mist environment that may exist in a battery room, polytetrafluoroethylene powder can effectively block the contact between sulfuric acid molecules and the thermoplastic polyurethane elastomer matrix, preventing the sheath material from decomposing, swelling or discoloring. In an alkaline environment, such as near some energy storage systems that use alkaline electrolytes, polytetrafluoroethylene powder can also resist the erosion of strong alkaline ions. Experiments show that after the cable using this new composite sheath is immersed in a 10% sulfuric acid solution and a 20% sodium hydroxide solution for 2000 hours, the material mass loss rate is less than 0.5%, while the mass loss rate of traditional polyvinyl chloride sheath materials under the same conditions can reach more than 20%.

[0037] In this embodiment, a high-performance thermoplastic polyurethane elastomer is selected as the base polymer. The thermoplastic polyurethane elastomer has a unique microphase separation structure, which is composed of a hard segment and a soft segment. The hard segment provides strength and wear resistance, and the soft segment gives the material good flexibility and elasticity. This structure enables the thermoplastic polyurethane elastomer to have high mechanical properties while maintaining excellent flexural resistance, and can adapt to the deformation requirements of the cable under different working conditions;

[0038] By adding polytetrafluoroethylene powder as an anti-corrosion additive. Polytetrafluoroethylene has extremely excellent chemical inertness and is highly resistant to almost all strong acids, strong bases, strong oxidants and organic solvents. Its powder form can be evenly dispersed in the thermoplastic polyurethane elastomer matrix to form a microscopic anti-corrosion barrier. When the cable sheath is corroded by corrosive media, polytetrafluoroethylene powder can prevent the penetration of corrosive ions and effectively protect the integrity of the sheath material.

[0039] By introducing high-strength aramid fiber as a reinforcing material, aramid fiber has ultra-high strength and modulus, and its strength is several times that of steel wire. It also has good heat resistance and chemical corrosion resistance. The aramid fiber is evenly distributed in a high-performance thermoplastic polyurethane elastic matrix in a specific weaving method or in the form of short fibers, which can significantly improve the tensile strength and tear resistance of the sheath material.

[0040] By adding an appropriate amount of benzotriazole anti-ultraviolet agents, this type of anti-ultraviolet agent can absorb ultraviolet energy and convert it into harmless heat energy and dissipate it, effectively preventing ultraviolet rays from causing photoaging to the sheath material and extending the service life of the sheath.

[0041] Embodiment 3: According to Figure 7-8As shown, the surface sheath B401 of one end of the wire A102 and the wire B103 connected to the connecting component 400, the outer surfaces of the connecting component 400 and the sheath B401 are coated with a coating C402, the surface of the sheath B401 is tin-plated, and the tin-plated layer on the surface of the wire A102 and the wire B103 can effectively prevent the corrosion of copper in an acidic or alkaline environment. In some energy storage systems, such as in an environment containing acidic or alkaline mist, the tin-plated layer can form a barrier to prevent corrosive substances from contacting the copper conductor. The tin-plated layer after passivation treatment further improves its corrosion resistance and oxidation resistance, and can maintain stable performance during long-term use. The material of coating C402 is nano-titanium dioxide. The nano-titanium dioxide coating on the surface of connecting component 400 has excellent antibacterial and anti-fouling properties. In the energy storage system, connecting component 400 may be exposed to a humid, dusty or microbially rich environment. The nano-coating can prevent microorganisms from growing on the surface and avoid corrosion problems caused by microbial metabolites. At the same time, the super-hydrophilic or super-hydrophobic properties of the nano-coating can be adjusted according to actual needs. The super-hydrophobic nano-coating can make the surface of connecting component 400 have a self-cleaning function, reduce dirt accumulation, and maintain good contact performance of connecting component 400, thereby improving the reliability and stability of the cable connection.

[0042] In this embodiment, the surfaces of the wire A102, the wire B103 and the connecting component 400 are first tin-plated to form a dense tin protective layer. Tin has high chemical stability and good corrosion resistance in general acid and alkali environments, and can effectively prevent the copper conductor from being corroded. Then, the tin-plated layer is passivated to further improve its corrosion resistance and oxidation resistance. The passivation treatment can form a dense oxide film on the surface of the tin-plated layer to prevent corrosive substances from directly contacting the tin layer.

[0043] By using nanotechnology to coat a layer of nano titanium dioxide coating on the surface of the connecting component 400, the nano coating has excellent antibacterial and anti-fouling properties, and can prevent corrosion and poor contact caused by microbial growth or dirt accumulation on the surface of the connecting component 400. At the same time, the super hydrophilic or super hydrophobic properties of the nano coating can be adjusted according to actual needs. For example, the super hydrophobic nano coating can make the surface of the connecting component 400 have a self-cleaning function and reduce the adhesion of moisture and corrosive substances on the surface.

[0044] The use method and working principle of this device: by adopting a multi-layer twisted conductor structure, for example, the inner layer adopts soft annealed copper wire to ensure good conductivity; the outer layer adopts specially treated high-strength aluminum alloy wire for twisting, and the surface of the aluminum alloy wire is nickel-plated to improve its corrosion resistance and oxidation resistance. This multi-layer twisted structure not only ensures the good conductivity of the conductor, but also significantly improves the tensile strength of the conductor. When the cable is subjected to tensile force, the outer layer of aluminum alloy wire can bear most of the tensile force and protect the inner layer of copper wire from damage;

[0045] By arranging a high-strength carbon fiber rod as a central reinforcement at the center of the conductor layer 100, the carbon fiber rod has extremely high strength and modulus, is light in weight, and has good corrosion resistance. It can provide additional support and tensile strength for the conductor, effectively preventing the conductor from breaking or deforming when subjected to a large tensile force. At the same time, the low thermal expansion coefficient of the carbon fiber rod helps to reduce the internal stress changes of the conductor caused by temperature changes, thereby improving the stability of the conductor.

[0046] The inner protective plate 201, the support frame 202 and the outer protective plate 203 are made of polypropylene, which has high corrosion resistance, good mechanical strength and excellent electrical insulation performance. Polypropylene is often used in light support frames 202 and is suitable for cables with high requirements for temperature resistance and corrosion resistance.

[0047] By wrapping a layer of high-strength polyester braided tape 205 outside the insulation layer, the polyester braided tape 205 has good mechanical properties. Its high strength and high toughness can provide effective protection for the insulation layer when the cable is squeezed or bent by external force to prevent the insulation layer from being damaged. At the same time, the mesh structure of the braided tape 205 can also disperse external forces to a certain extent and reduce local stress concentration.

[0048] By selecting high-performance thermoplastic polyurethane elastomer as the base polymer, the thermoplastic polyurethane elastomer has a unique microphase separation structure, which consists of hard segments and soft segments. The hard segment provides strength and wear resistance, while the soft segment gives the material good flexibility and elasticity. This structure enables the thermoplastic polyurethane elastomer to have high mechanical properties while maintaining excellent flexural resistance, and can adapt to the deformation requirements of the cable under different working conditions;

[0049] By adding polytetrafluoroethylene powder as an anti-corrosion additive. Polytetrafluoroethylene has extremely excellent chemical inertness and is highly resistant to almost all strong acids, strong bases, strong oxidants and organic solvents. Its powder form can be evenly dispersed in the thermoplastic polyurethane elastomer matrix to form a microscopic anti-corrosion barrier. When the cable sheath is corroded by corrosive media, polytetrafluoroethylene powder can prevent the penetration of corrosive ions and effectively protect the integrity of the sheath material.

[0050] By introducing high-strength aramid fiber as a reinforcing material, aramid fiber has ultra-high strength and modulus, and its strength is several times that of steel wire. It also has good heat resistance and chemical corrosion resistance. The aramid fiber is evenly distributed in a high-performance thermoplastic polyurethane elastic matrix in a specific weaving method or in the form of short fibers, which can significantly improve the tensile strength and tear resistance of the sheath material.

[0051] By adding an appropriate amount of benzotriazole anti-ultraviolet agents, this type of anti-ultraviolet agent can absorb ultraviolet energy and convert it into harmless heat energy and dissipate it, effectively preventing ultraviolet rays from causing light aging to the sheath material and extending the service life of the sheath;

[0052] The surfaces of the wire A102, the wire B103 and the connecting component 400 are first tin-plated to form a dense tin protective layer. Tin has high chemical stability and good corrosion resistance in general acid and alkali environments, and can effectively prevent the copper conductor from being corroded. Then, the tin-plated layer is passivated to further improve its corrosion resistance and oxidation resistance. The passivation treatment can form a dense oxide film on the surface of the tin-plated layer to prevent corrosive substances from directly contacting the tin layer.

[0053] By using nanotechnology to coat a layer of nano titanium dioxide coating on the surface of the connecting component 400, the nano coating has excellent antibacterial and anti-fouling properties, and can prevent corrosion and poor contact caused by microbial growth or dirt accumulation on the surface of the connecting component 400. At the same time, the super hydrophilic or super hydrophobic properties of the nano coating can be adjusted according to actual needs. For example, the super hydrophobic nano coating can make the surface of the connecting component 400 have a self-cleaning function, reducing the adhesion of moisture and corrosive substances on the surface;

[0054] Through the design of three innovative points in anti-corrosion energy storage cables in terms of anti-corrosion, tensile and compressive resistance, and wear resistance, namely, the use of new composite materials as sheaths, optimization of the internal reinforcement structure of cables, and the use of special surface treatment technologies, and in-depth analysis of the structure and function of each innovative point, the following conclusions can be drawn: These innovative designs have comprehensively improved the performance of energy storage cables from multiple dimensions. In terms of anti-corrosion performance, whether it is the innovation of sheath materials, the optimization of internal reinforcement structures, or the application of surface treatment technologies, they have effectively resisted the erosion of various corrosive media; in terms of tensile and compressive performance, through the improvement of conductor structure, the setting of internal reinforcements, and the strengthening of sheath materials, the cables can withstand greater mechanical stress; in terms of wear resistance, the special design of sheath materials and surface coating treatment significantly improve the wear resistance of cables. This new type of anti-corrosion energy storage cable can better meet the application needs of modern energy storage systems in complex and harsh environments, has broad market prospects and application value, and provides strong technical support for the development of the energy storage industry. In future research, the material and process parameters of each innovation point can be further optimized, and the integrated application of more new materials and technologies can be explored to achieve higher performance, more economical and environmentally friendly anti-corrosion energy storage cable products, and promote continuous progress in the field of energy storage technology.

[0055] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-corrosion energy storage cable, characterized in that: The invention comprises a conductor layer (100), a pressure-resistant layer (200), a sheath layer (300) and a connecting component (400): the conductor layer (100) comprises a tensile rope (101), a conductor A (102) is arranged on the outer surface of the tensile rope (101), a conductor B (103) is sleeved on the outer surface of the conductor A (102), a shielding sleeve (104) is arranged on the outer surface of the conductor B (103), an insulating sleeve (105) is sleeved on the outer surface of the shielding sleeve (104), the pressure-resistant layer (200) comprises an inner protective plate (201), a support frame (202) is fixedly mounted on the outer surface of the inner protective plate (201), an outer protective plate (203) is fixedly mounted on the outer surface of the support frame (202), a buffer block (204) is arranged between the outer protective plate (203) and the inner protective plate (201), and a braided belt (205) is arranged on the outer surface of the outer protective plate (203).

2. The anti-corrosion energy storage cable according to claim 1, characterized in that: The conductor A (102) adopts a multi-layer twisted structure and is made of soft annealed copper wire. The conductor B (103) is made of nickel-plated aluminum alloy wire. The tensile rope (101) is made of carbon fiber rod.

3. The anti-corrosion energy storage cable according to claim 1, characterized in that: The shielding sleeve (104) is made of aluminum foil, the insulating sleeve (105) is made of natural rubber, and the braided belt (205) is made of polyester.

4. The anti-corrosion energy storage cable according to claim 1, characterized in that: The inner shapes of the inner guard plate (201), the outer guard plate (203) and the buffer block (204) are all honeycomb-shaped, and the materials of the inner guard plate (201), the support frame (202) and the outer guard plate (203) are all polypropylene.

5. The anti-corrosion energy storage cable according to claim 1, characterized in that: The number of the buffer blocks (204) is eight groups, and the eight groups of buffer blocks (204) are evenly distributed between the inner protective plate (201) and the outer protective plate (203). The material of the buffer blocks (204) is polyurethane foam.

6. The anti-corrosion energy storage cable according to claim 1, characterized in that: The sheath layer (300) comprises a sheath A (301), the outer surface of the sheath A (301) is coated with a coating A (302), and the outer surface of the coating A (302) is coated with a coating B (303).

7. The anti-corrosion energy storage cable according to claim 6, characterized in that: The material of the sheath A (301) is thermoplastic polyurethane elastomer as a base polymer, polytetrafluoroethylene is added as an anti-corrosion additive, high-strength aramid fiber is introduced as a reinforcing material, and an appropriate amount of benzotriazole anti-ultraviolet agent is added therein. The material of the coating A (302) is ceramic.

8. The anti-corrosion energy storage cable according to claim 6, characterized in that: The material of the coating B (303) is polyurethane containing a microcapsule repair agent.

9. The anti-corrosion energy storage cable according to claim 1, characterized in that: The surface sheath B (401) of one end of the wire A (102) and the wire B (103) connected to the connecting component (400) is provided, and the outer surfaces of the connecting component (400) and the sheath B (401) are both coated with a coating C (402).

10. The anti-corrosion energy storage cable according to claim 9, characterized in that: The surface of the sheath B (401) is tin-plated, and the material of the coating C (402) is nano-titanium dioxide.

Citation Information

Patent Citations

  • cable

    CN110473669B

  • Mixed conductor environment-friendly type wind power cable and production process

    CN106847388A

  • Water-blocking molded line stranded power cable

    CN116779217A

  • Heat -resisting flexible photovoltaic cable

    CN206505765U

  • Wear-resistant aluminum alloy cable

    CN209625863U

Cited By

  • High-flame-retardant temperature-resistant corrosion-resistant optical fiber composite cable and preparation method thereof

    CN121260576A